Propositional Meaning in the Kelan Beach Warning Banner: A Landscape Linguistic Study - Polce Aryanto Bessie; Maria Beatrix Rahinart Wellalangi; Dominikus Seno; Akib Hehanussa (e-Journal of Linguistics, 2025)
This research aims to find the mental meaning of the lexicon contained in the Kelan beach information banner and also the construction of words and sentences on the text of the Kelan beach information banner. This research is a qualitative study. This research uses the language image theory proposed by Witgenstein, 1983 in Starks 2019 and the Proposition theory by Van Dijk 1983. Apart from that, Stylistics theory is also used to look at the language styles contained in the text. The results of the research show that the words contained in the attached text contain a mixture of colloquial loan words such as healing and sunset. Sentence construction is also a type of spoken language sentence where the subject of the sentence is not included but the reader is placed as the subject. Furthermore, there are consecutive verbs in sentence construction, but all of these verbs carry noun meanings.